Genetic fusion to albumin improves the pharmacokinetic properties of factor IX - Metzner, Hubert J.; Weimer, Thomas; Kronthaler, Ulrich; Lang, Wiegand; Schulte, Stefan (Thrombosis and Haemostasis, 2009)
Haemophilia B is a X-chromosome linked disease characterised by a deficiency of functionally active coagulation Factor IX (FIX). Patients with severe haemophilia B at risk of recurrent bleeding are treated approximately twice a week in a prophylactic setting by application of FIX concentrates.To increase convenience and compliance of the therapy it is desirable to reduce the dosing frequency by improving the pharmacokinetic properties of FIX. Here a concept of rFIX (recombinant factor IX) albumin fusion proteins (rIX-FPs) with cleavable linker peptides derived from the FIX activation sequence is presented. Constructs of the genetic fusion of FIX to albumin via cleavable linkers were expressed in mammalian cells and characterised after purification. In vitro activation studies with FXIa demonstrated that cleavage of the linker and the activation peptide proceeded comparably well. In a clotting assay the rIX-FPs with cleavable linker showed a 10- to 30-fold increase in the molar specific clotting activity compared to fusion proteins with non-cleavable linkers. Furthermore, in-vivo recovery, terminal half-life and the AUC of rIX-FPs in rats and rabbits as determined by FIX antigen measurements were significantly increased compared to rFIX (BeneFIX®). In FIX deficient (FIX−/−) mice the in-vivo recovery and the AUC were also significantly increased.The efficacy in reducing bleeding time was shown in FIX−/−mice by a tail tip bleeding model. The results suggest that rIX-FPs with a cleavable linker between FIX and albumin are a promising concept that may support the use of the albumin fusion technology to extend the half-life of FIX.
Keywords: FIX; albumin fusion; rIX-FP; coagulation